Cigarette price and other factors associated with brand choice and brand loyalty in Zambia: findings from the ITC Zambia Survey. (28th January 2015) - Salloum, Ramzi G; Goma, Fastone; Chelwa, Grieve; Cheng, Xi; Zulu, Richard; Kaai, Susan C; Quah, Anne C K; Thrasher, James F; Fong, Geoffrey T
Abstract : Objectives: Little is known about cigarette pricing and brand loyalty in sub-Saharan Africa. This study examines these issues in Zambia, analysing data from the International Tobacco Control (ITC) Zambia Survey. Methods: Data from Wave 1 of the ITC Zambia Survey (2012) were analysed for current smokers of factory-made (FM) cigarettes compared with those who smoked both FM and roll-your-own (RYO) cigarettes, using multivariate logistic regression models to identify the predictors of brand loyalty and reasons for brand choice. Results: 75% of FM-only smokers and 64% of FM+RYO smokers reported having a regular brand. Compared with FM-only smokers, FM+RYO smokers were, on average, older (28% vs 20% ≥40 years), low income (64% vs 43%) and had lower education (76% vs 44% < secondary). Mean price across FM brands was ZMW0.50 (US$0.08) per stick. Smokers were significantly less likely to be brand loyal (>1 year) if they were aged 15–17 years (vs 40–54 years) and if they had moderate (vs low) income. Brand choice was predicted mostly by friends, taste and brand popularity. Price was more likely to be a reason for brand loyalty among FM+RYO smokers, among ≥55-year-old smokers and among those who reported being more addicted to cigarettes. Conclusions: These results in Zambia document the high levels of brand loyalty in a market where price variation is fairly small across cigarette brands. Future research is needed on longitudinal trends to evaluate the effect of tobacco control policies in Zambia.